Characterization of phenoloxidase of Penaeus indicus - Anil Kumar, P; Sridhar, N (Indian Journal of Fisheries, 2011)
Quinone-tanned proteins or sclerotins are important structural proteins of invertebrate exoskeletons. The role of the enzyme phenol oxidase in sclerotin formation was explained by Pryor (1940 a b) and since then it has been widely reported in parasites (Mansour 1958, Nellaiappan et al. 1989 a, b), insects (Hackman and Goldberg 1967, Yamazaki 1969, Pau et al. 1971, Brunet 1980) and molluscs (Waite and Wilbur 1976, Bharati and Ramalingam 1983). In Crustaceans it was studied mainly in crabs (Summers 1967, Vacca and Fingerman 1975, Nellaiappan et al. 1982)